Rutter Parkway documentation, - Emerson, Stephen
Photographs and description of the stone markets near the western end of the Rutter Parkway, located about 5 miles north of Spokane. The stone markers were slated for removal by the Washington State Department of Transportation In 2004 due to a road realignment. The report in this collection describes the markers, the history of their construction by the Civilian Conservations Corps in 1938. Stephen Emerson of Archaeological and Historic Services documented the Rutter Parkway before the realignment project.